Spatiotemporal phase slip patterns for visual evoked potentials, covert object naming tasks, and insight moments extracted from 256 channel EEG recordings - Ramon, Ceon; Graichen, Uwe; Gargiulo, Paolo; Zanow, Frank; Knösche, Thomas R.; Haueisen, Jens (Frontiers in Integrative Neuroscience, 2023)
Phase slips arise from state transitions of the coordinated activity of cortical neurons which can be extracted from the EEG data. This becomes an additional biomarker to study the cognitive behavior of the brain. The phase slip rates (PSRs) were studied from the high density (256 channel) EEG data, sampled at 16.384 kHz, of five adult subjects during covert visual object naming tasks. Artifact-free data of 29 trials were averaged for each subject. The analysis was performed to look for phase slips in the theta (4-7 Hz), alpha (7-12 Hz), beta (12-30 Hz) and low gamma (30-49 Hz) bands. The phase was calculated with Hilbert transform, then unwrapped and detrended to look for phase slip rates in ms wide stepping windows with a step size of 0.06 ms. The spatiotemporal plots of the PSRs were made by using a montage layout of 256 equidistant electrode positions. The spatiotemporal profiles of EEG and PSRs during the stimulus and during the first second of the poststimulus period were examined in detail to study the visual evoked potentials and different stages of visual object recognition in the visual, language and memory areas of the brain. The P1-N1-P2 complex of visual evoked potentials was easily identifiable in the stimulus period. It was found that activity areas of PSRs were slightly different as compared with EEG activity areas during the stimulus and poststimulus periods. Different stages of the insight moments during the covert object naming tasks were examined from PSRs and it was found to be about 512±21 ms for the ‘Eureka’ moment. Over all, these results indicate that information about the cortical phase transitions can be derived for the measured EEG data and can be used in a complimentary fashion to study the cognitive behavior of the brain.